(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: Intense The economic units are suffering from intense competition as a result of the developments that the world has witnessed in the technological field, which has resulted in an increase in the costs of their products, which has prompted these units to search for contemporary administrative means that enable them to keep pace and adapt to the changes and developments that have occurred in the business environment. Accordingly, these units began searching for these means that would enable them to keep pace with the accelerating events in the business environment, as it enabled management to manage the costs of its products in a way that achieves and maintains customer satisfaction. One of these means is the continuous improvement budget, as this budget is built on the basis of the philosophy that improvements, whatever they are, constitute an impact that enables economic units to become leaders in the market, as continuous improvement includes improving the business environment of processes, people, materials, and production methods, as well as the process of Its success is achieved with the support of senior management. In order to support senior management in implementing this budget, it was necessary to prepare estimated budgets amended with the improvements that will be implemented in the future and in a manner consistent with continuous improvement. These budgets are prepared based on the specific improvement percentages for production and the percentage for reducing production, and these percentages are determined based on the opinions of workers in the company. The economic unit and the goals set by senior management, meaning that these ratios are filled in for the administrative accountant, who in turn collects the costs and any numbers resulting from the improvement and coordinates them within the continuous improvement budget . The aim of this research is to enable economic units to use the continuous improvement budget and manage the costs of their products. The continuous improvement budget is prepared based on a philosophy of improvements that include the business environment of processes, people, materials and production methods. After studying the continuous improvement budget, it was concluded that using the budget It will achieve effective control over costs and a means to achieve the goals of economic units by reducing them through setting estimated numbers that are formulated in accordance with the continuous improvements taking place within the work halls improvement budget.